Cotton seeds treated with systemic fungicides in the control of damping-off - Carvalho, Julita Maria Frota Chagas; Lima, Emídio Ferreira; de Carvalho, Luiz Paulo; Cavalcante, Fernando Bezerra; Carvalho, Orozimbo Silveira (Pesquisa Agropecuaria Brasileira, 2014)
The control of the canon seedling damping-off caused by Rhizoctonia solani and Colletotrichum gossypii var. cephalosporioides was evaluated in cotton seed samples, cv. BR-1, treated with eleven combinations of fungicides, in six storage periods. The combinations of fungicides Benlate + Captan (0.50 + 1.00 g) was the most eficient in the control of damping-off caused by R. solani and C. gossypii. In soil infested by both fungi good control was obtained by the use of Captan + Cycosin (1,00 + 0.50 g), Brassicol + Benlate + Captan (0.66 + 0.50 + 1.00 g) and Vitavax + Captan (1.00 + 0.50 g). In periods of low temperature and high relative humidity the combination of Vitavax + Captan (1.00 + 0.50 g) gave the most effective control when R. solani, C. gossypii and both fungi were together. No efficacy loss was observed in the mixture of fungicides with the increase of storage time up to 120 days.